2013
DOI: 10.1186/1471-2407-13-220
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus-associated oropharyngeal cancer: an observational study of diagnosis, prevalence and prognosis in a UK population

Abstract: BackgroundThe incidence of Human Papillomavirus (HPV) associated oropharyngeal cancer (OPC) is increasing. HPV-associated OPC appear to have better prognosis than HPV-negative OPC. The aim of this study was to robustly determine the prevalence of HPV-positive OPC in an unselected UK population and correlate HPV positivity with clinical outcome.MethodsHPV testing by GP5+/6+ PCR, In Situ Hybridisation (ISH) and p16 immunohistochemistry (IHC) was performed on 138 OPCs diagnosed in South Wales (UK) between 2001–06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
81
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 23 publications
12
81
1
8
Order By: Relevance
“…Previous small, single centre studies from the UK reported HPV prevalence rates in OPSCC of 37.5% (95% CI:28, 48%), 42.7% (95% CI:36, 50%), and 55% (95% CI:45, 66%). [12][13][14] The current study is consistent with these, but is based on a much larger sample with broader geographical representation, including centres in all four countries of the UK. We observed a consistent proportion of HPV-positive OPSCC over time from 2002 to 2011, against a background of increasing incidence.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous small, single centre studies from the UK reported HPV prevalence rates in OPSCC of 37.5% (95% CI:28, 48%), 42.7% (95% CI:36, 50%), and 55% (95% CI:45, 66%). [12][13][14] The current study is consistent with these, but is based on a much larger sample with broader geographical representation, including centres in all four countries of the UK. We observed a consistent proportion of HPV-positive OPSCC over time from 2002 to 2011, against a background of increasing incidence.…”
Section: Discussionsupporting
confidence: 64%
“…[7][8][9][10][11] In the UK, the proportion of OPSCC attributable to HPV has been assessed in several single-centre studies, however each was small, applied diverse methodology and had restricted geographical coverage. [12][13][14] The current pan-UK study aimed to assess the proportion of OPSCC attributable to HPV infection in a large contemporary sample (2002-2011 inclusive) using robust, standardised methods. There is a pressing need for these data to facilitate health economic analyses and to inform evidence-based policy-making with regard to prophylactic male HPV vaccination, as has recently been implemented in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto a la edad, aunque no se encontraron diferencias estadísticamente significativas y la mayoría de los pacientes era mayor de 50 años, se encontró una tendencia a registrar una mayor prevalencia de la infección con HPV en las personas entre los 31 y los 40 años de edad, lo cual también corrobora otros estudios en los que, generalmente, los casos positivos para HPV se presentan más entre las personas más jóvenes (6,10,28).…”
Section: Cuadro 3 Transcritos De E7 Obtenidos De Las Nueve Muestrasunclassified
“…La incidencia del cáncer de células escamosas en la cavidad oral inducido por HPV aumenta cada año, con tasas de prevalencia que fluctúan entre 36 y 80 %, dependiendo de la ubicación geográfica y la región anatómica (9)(10)(11)(12). En Colombia solo se ha publicado el estudio sobre cáncer de cabeza y cuello asociado a HPV llevado a cabo por Quintero, et al, en el cual se registró una prevalencia de HPV de 18,9 % (13).…”
unclassified
“…In Europe, there were approximately 250,000 cases and 63,500 deaths in 2012 [4]. A 2013 study designed to determine the prevalence of HPV-positive oropharyngeal cancer in an unselected UK population detected HPV in 55% of patients [5].…”
Section: Introductionmentioning
confidence: 99%